Growing a hydrophilic nanoporous shell on a hydrophobic catalyst interface for aqueous reactions with high reaction efficiency and: In situ catalyst recycling - Hao, Y.; Jiao, X.; Zou, H.; Yang, H.; Liu, Jian (R S C Publications, 2017)
Â© 2017 The Royal Society of Chemistry. The structure of biological components such as enzymes with active centers buried in hydrophobic pockets has inspired the design of new nanoreactors for efficient chemical processes. To address the current limitations of conventional hydrophobic catalysts or hydrophilic ones, herein, we reported the synthesis of core-shell structured catalysts with Pd-loaded fluoro-modified silica spheres as hydrophobic cores and mesoporous silicas as hydrophilic shells. The resultant nanoreactors allow the catalyst to not only be well dispersed in water but also be able to adsorb hydrophobic reactants to its active centers from water, which makes the catalyst exhibit much higher activity than its analogous catalyst Pd/SiO 2 in the aqueous hydrogenation of olefins. Moreover, at the end of the reaction, we demonstrated that this nanoreactor can be directly used for the next reaction cycle after the removal of the upper layer of the organic product, making in situ catalyst recycling possible. Such a process significantly decreases the loss of the catalyst during recycling, which is unattainable for conventional catalyst separation methods such as filtration and centrifugation. After 12 reaction cycles, its activity has no significant decrease. These results illustrate the preparation of efficient solid catalysts for innovative green and sustainable chemical processes.